2019
DOI: 10.1016/j.ejpb.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel microfluidic-based approach to formulate size-tuneable large unilamellar cationic liposomes: Formulation, cellular uptake and biodistribution investigations

Abstract: Extensive research has been undertaken to investigate the effect of liposome size in vitro and in vivo.However, it is often difficult to generate liposomes in different size ranges that offer similar low polydispersity and lamellarity. Conventional methods used in the preparation of liposomes, such as lipid film hydration or reverse phase evaporation, generally give rise to liposomal suspensions displaying broad, multimodal size distribution combined with uncontrolled degree of lamellarity. In contrast, microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 48 publications
3
37
0
1
Order By: Relevance
“…It is hypothesised that the reactive amine group within the TRIS structure becomes protonated, resulting in cationic zeta potentials. Moreover, the effect that buffer type and concentration have on liposomal systems produced using microfluidics has been previously explained by Lou et al [39]. Lou et al demonstrated that DSPC:Chol:DOTAP liposomes were larger (approx.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is hypothesised that the reactive amine group within the TRIS structure becomes protonated, resulting in cationic zeta potentials. Moreover, the effect that buffer type and concentration have on liposomal systems produced using microfluidics has been previously explained by Lou et al [39]. Lou et al demonstrated that DSPC:Chol:DOTAP liposomes were larger (approx.…”
Section: Discussionmentioning
confidence: 82%
“…100 nm) when prepared using citrate buffer pH 6 compared to TRIS buffer pH 7.4 (approx. 60 nm) even at the same buffer molarity [39]. Particle size was dependent on buffer type, concentration and cationic lipid content.…”
Section: Discussionmentioning
confidence: 89%
“…We also show that alcohol mixtures can be used to fine-tune the liposome size. We have previously shown that buffer concentration can be used to offer size control [18]. Therefore, liposome size is under the influence of alcohol and the salt concentration of the aqueous buffer and both are key process parameters that should be considered in the development of microfluidic manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, we have demonstrated the ability to entrap small molecules [10,11], nucleic acids [12] and proteins [13,14] within liposomes. We have also demonstrated the scale-independent production of liposomal adjuvants using this method [15][16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…Lipid composition and complexation with pDNA could influence the size of CLs and zeta potential and hence biodistribution and cellular entry. 158 , 159 , 160 Particles smaller than 5 or 50 nm are easily excreted by urine or lodged in the liver, respectively. 90 However, particles larger than 50 nm are difficult to penetrate deep into the tumor and thus reduce cellular uptake.…”
Section: Main Textmentioning
confidence: 99%